Writing About Harry Potter Boinking: The Reality of Fantasy in Pornographic Fanfiction - Santos, Maria (Université d'Ottawa | University of Ottawa, 2014)
With the advent of participatory culture or Web 2.0, fans are flocking to the Internet in increasing numbers in order to write stories about their favorite characters from books, movies or television shows having sex. While this participation with primary media was primarily dismissed by fan and pornography scholars, more recent studies on pornographic fanfiction argue that this activity is an empowering one. This reception study purports to answer how the creation of these stories benefits their lives. Using content analysis techniques, this study examines fan discourse on online forums about writing pornographic fanfiction and it is concluded that their play with reality and fantasy has benefits on their offline lives in an emotional and sexual sense. Recently as well as historically, pornography scholars have suggested that authenticity is the key factor in determining quality products, and this study suggests that experimentation across the boundaries of what is real and not real leads to present and future benefits for fan's lives.